Metode Rapid Application Development (RAD) Dalam Merancang Website Top Up - Aulianita, Rizki; Mukhayaroh, Anna (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2025)
The development of information and communication technology, particularly the internet, has had a significant impact on various sectors, including e-commerce. One of the rapidly growing aspects is online buying and selling systems, especially game saldo top-up transactions. Top-up websites serve as platforms that facilitate users in purchasing game vouchers quickly and efficiently. This study aims to design and implement a top-up website using the CodeIgniter 3 framework with the Rapid Application Development (RAD) method approach, which enables faster software development through direct user involvement at every stage. The development process of the website begins with system requirement analysis, followed by user interface design, system development using CodeIgniter, and concludes with testing. Using RAD, the development is done iteratively with direct feedback from users, resulting in a system that better meets user needs. The website includes key features such as member registration, game selection, voucher purchase, and payment confirmation integrated with WhatsApp. The implementation uses PHP, CodeIgniter, and MySQL. The results of the study show that the use of the RAD method successfully accelerates development without compromising quality, making the website an easier platform with a simple and user-friendly interface. Keywords : Website, CodeIgniter, RAD